1997
DOI: 10.1111/0019-8676.00064
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pay and Work Conditions on Farmworker Retention

Abstract: Whether a seasonal farmworker returns to an employer in the following year depends on decisions by both the worker and the employer. Employers are more likely to rehire prime age, experienced, foreign-born workers. An employer increases the probability that a worker returns by spending the last dollar of compensation on benefits or improving working conditions rather than on higher wages. WHETHER A FARM EMPLOYER RETAINS last year's employees to work this year's crop depends on decisions by both employer and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
8
1
Order By: Relevance
“…Workers' retention rates were expressed as a percentage of the workers who were employed in the same nursery or greenhouse for the past 2 years before the interviews. Gabbard and Perloff (1997) reported that farmworkers are more likely to return to employers who offer benefits, pay by the hour, provide good working conditions, and hire directly. The WRI was expected to be positive because automation or mechanization would improve professional esteem and work satisfaction as a result of better and safer working conditions.…”
Section: Empirical Modelsmentioning
confidence: 99%
“…Workers' retention rates were expressed as a percentage of the workers who were employed in the same nursery or greenhouse for the past 2 years before the interviews. Gabbard and Perloff (1997) reported that farmworkers are more likely to return to employers who offer benefits, pay by the hour, provide good working conditions, and hire directly. The WRI was expected to be positive because automation or mechanization would improve professional esteem and work satisfaction as a result of better and safer working conditions.…”
Section: Empirical Modelsmentioning
confidence: 99%
“…The retention of seasonal farmworkers depends on decisions by the workers and the employers. Gabbard and Perloff (1997) suggested that employers are more likely to rehire prime age, experienced, foreign-born workers and that the probability that a worker returns is increased by spending the last dollar of compensation on benefits or improving working conditions rather than on higher wages. Posadas (2012) observed exceedingly high workers' retention rates among the participating wholesale operations with no significant variations among various types of operations.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the only research available in South Africa in from 1957 on the labour turnover of urban "native" (black African) workers in Cape Town, which included farm workers (van der Horst, 1957). Internationally, there are only four studies on the labour turnover of farm workers, one on tobacco farms in Canada (Smit et al, 1985), two on farms in the USA (Taylor and Thilmany, 1993;Gabbard and Perloff, 1997) and a fourth on secondary analyses of the National Agricultural Workers Survey (NAWS) in the USA (Mines et al, 1991). These findings suggest that temporary farm workers leaving employment before completing the harvesting season are predominantly men, aged under 26, non-locals, inexperienced and/or recruited through employment centres (Smit et al, 1985, p. 166).…”
Section: Literature Review and Rationalementioning
confidence: 99%
“…From secondary analyses of the NAWS, Gabbard and Perloff (1997) suggest that farms in the USA retain 40 per cent of their temporary employees (p. 478). Retention was higher amongst single temporary farm workers and those unable to speak English.…”
Section: Literature Review and Rationalementioning
confidence: 99%